2020
DOI: 10.5812/hmj.101124
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aromatherapy by Rose Essence on Anxiety and Physiological Indices of Conscious Patients Admitted at Intensive Care Units

Abstract: Background: Anxiety in patients admitted at the Intensive Care Unit (ICU) is common and usually moderate or severe. Anxiety affects endocrine and physiological responses. Objectives: This study aimed to determine the effect of aromatherapy by rose essence on anxiety and physiological indices of conscious patients admitted at ICU. Methods: In this clinical trial, 60 conscious patients admitted at ICU wards in Ali Ibn Abi Talib Hospital of Rafsanjan were selected and randomly allocated into two groups of interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Spielberger state–trait anxiety inventory (STAI) was used in 16 studies, seven of which used both trait anxiety inventory (TAI, score: 20–80) and state anxiety inventory (SAI, score: 20–80) (Abbasijahromi et al, 2020; Babaii et al, 2015; Barati et al, 2016; Fazlollahpour‐Rokni et al, 2019; Haehner et al, 2017; Najafi et al, 2020; Sadeghi et al, 2020). Furthermore, SAI was applied in nine studies (Babatabar Darzi et al, 2020; Bikmoradi et al, 2020; Dagli et al, 2019; Gholami et al, 2019; Hamdamian et al, 2018; Jodaki et al, 2021; Setayeshvali Pour et al, 2012; Tazakori et al, 2016; Zare et al, 2020). Out of the seven studies that used both dimensions of STAI, one with the posttest‐only control group design was not included in the meta‐analysis (Haehner et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spielberger state–trait anxiety inventory (STAI) was used in 16 studies, seven of which used both trait anxiety inventory (TAI, score: 20–80) and state anxiety inventory (SAI, score: 20–80) (Abbasijahromi et al, 2020; Babaii et al, 2015; Barati et al, 2016; Fazlollahpour‐Rokni et al, 2019; Haehner et al, 2017; Najafi et al, 2020; Sadeghi et al, 2020). Furthermore, SAI was applied in nine studies (Babatabar Darzi et al, 2020; Bikmoradi et al, 2020; Dagli et al, 2019; Gholami et al, 2019; Hamdamian et al, 2018; Jodaki et al, 2021; Setayeshvali Pour et al, 2012; Tazakori et al, 2016; Zare et al, 2020). Out of the seven studies that used both dimensions of STAI, one with the posttest‐only control group design was not included in the meta‐analysis (Haehner et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 27 included studies that measured anxiety, six evaluated objective indicators such as heart rate, respiratory rate, blood pressure, mean arterial pressure, and oxygen saturation (Bikmoradi et al, 2021; Dagli et al, 2019; Najafi et al, 2020; Noorian et al, 2020; Tazakori et al, 2016; Zare et al, 2020). Considering the limited number of studies that measured each indicator, it was impossible to pool the data using meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential oils or aromatherapy can be given to patients for 20 minutes using an oxygen mask, such as for those patients after undergoing CABG surgery. The results of other studies showed that the group that was given rose aromatherapy had less anxiety and was more relaxed (30,31).Research shows that patients who are given rose aromatherapy have less anxiety and feel more relaxed (30). Rose aromatherapy can reduce anxiety and increase relaxation, which affects the nervous and limbic systems so that the activity of the sympathetic nervous system is reduced (32).…”
Section: Sensory Therapiesmentioning
confidence: 99%